Analisis Komputasional Dinamika Fluida Pada Pipa Horizontal Pneumatik Konveyor Dengan Variasi Partikel - Sakal Hanov Dulvin Sinaga; Asral Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The conveying process of solid particles with air as a medium transport is commonly found in industries. Phenomenon that occurs and must be calculated appropriately is the pressure drop on pneumatic conveyor pipeline. Computational Fluid Dynamics is a system analysis that used to predict fluid flow. The pressure drop that occurs in horizontal pipeline with a length of 2 m, an inner diameter of 80 mm and a thickness of 4 mm is simulated with Euler-euler model. Pressure drop characteristics to particle mass flow rate, particle concentration, particle diameter and air velocity was investigated. The simulation was performed using Fluent 14.5. The results indicated that with the increase of mass flow rate of particles, particle diameter and air flow rate, the pressure drop will increase. Particle concentration does not have a considerable influence in the pressure drop on horizontal pipeline.Keywords : CFD, particles, pressure drop